High Frequency Non-invasive (HFNI) Bio-Sensors As a Potential Tool for Marine Monitoring and Assessments - Andrade, Hector; Massabuau, Jean-Charles; Cochrane, Sabine; Ciret, Pierre; Tran, Damien; Sow, Mohamedou; Camus, Lionel (Frontiers in Marine Science, 2016)
Marine ecosystems all over the globe are facing multiple simultaneous stressors including rapid climatic change and increased resource exploitation, such as fishing, petroleum exploration and shipping. The EU-funded DEVOTES project (DEVelopment Of innovative Tools for understanding marine biodiversity and assessing good Environmental Status) aims to better understand the relationships between pressures from human activities and climatic influences and their effects on marine ecosystems. To achieve these goals, it is necessary among others, to test and validate innovative monitoring tools to improve our understanding of ecosystem and biodiversity changes. This paper outlines the application of a high frequency non-invasive (HFNI) valvometer as a potential tool for long-term marine monitoring and assessments. The principle of the method is based on the regular gaping behaviour (closing and opening of the valves) of bivalve molluscs and the fact that physical or chemical stressors disrupt that gaping reference pattern. Bivalve gaping behaviour is monitored in the natural environment, remotely, continuously over a time period of years, requirements that must be fulfilled if bivalve behaviour is to be a useful biomonitoring tool. Here, we review the literature and highlight potential uses of the HFNI valvometry as a biosensor, to monitor and provide early-warning alerts of changes in water quality, such as global temperature increase, releases of contaminants and toxic algal blooms. Finally, potential relevant applications for monitoring and assessing environmental status of marine waters in the context of the Marine Strategy Framework Directive are identified. Relevant descriptors, Criteria and Indicators of Good Environmental Status that might be monitored using the HFNI valvometer are discussed for monitoring bathing beaches and harbours, petroleum installations and aquaculture sites.